Immunodepletion of α‐plurivorin effector leads to loss of virulence of Phytophthora plurivora towards Fagus sylvatica. Issue 5 (7th September 2017) - Dalio, R. J. D.; Fleischmann, F.; Chambery, A.; Eichmann, R.; Massola, N. S.; Pascholati, S. F.; Osswald, W.
Summary: Phytophthora species secrete several proteins during their interaction with plants. Some of these proteins manipulate host metabolism favouring infection, while others can be recognized by plants thus triggering defence. Elicitins are known to elicit plant defences, leading to resistance. Here, we characterized the elicitin α‐plurivorin and proved that it was essential for the virulence of Phytophthora plurivora towards Fagus sylvatica . The immunodepletion of this peptide impaired its penetration into host tissue and in parallel P. plurivora lost its ability to colonize beech roots. Furthermore, the lack of α‐plurivorin inside the host led to an up‐regulation of several defence‐related genes of both salicylic acid and jasmonate/ethylene pathways, suggesting that α‐plurivorin might act as an effector‐triggered susceptibility during infection. Consequently, plants survived infection with P. plurivora after α‐plurivorin immunodepletion, whereas the majority of the infected control plants had died at the end of the experiment. Because canonical elicitins are ubiquitously secreted by many Phytophthora species, it is possible that these molecules may play a similar role in other susceptible interactions, being a potential target for controlling Phytophthora diseases.